Who is a Refugee?: A Critical Assessment of the 1951 Geneva Convention - Ayşem Biriz Karaçay (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2023)
This article has been prepared to evaluate the adventure of the international protection system put forth by the 1951 United Nations Geneva Convention on the Legal Status of Refugees and its implementation by Turkey. The research, which is the culmination of a literature review and two online panels organized by GAR, discusses the modern asylum regime that emerged after the Second World War, in terms of the historical background, provisions, and implementation of the Convention. For, the fact that the inclusive international protection regimes are replaced by exclusionary policies that attempt to keep refugees and migrants away by forming a safe zone/country displays the course of the conspicuous change in the field from past to present. Hence, in this article, I have assessed whether the Convention produces durable solutions to extensive and complex population movements that neither abide by borders nor recognize the pressures in the face of externalization/security-oriented immigration/border policies that result in the erosion of protection of policies that secure the individual.